An Obsessive-Compulsive Symptom-Related Headache in a Patient with Schizophrenia - Yuan, Hsinsung; Liu, Junjun (Case Reports in Psychiatry, 2020)
Obsessive-compulsive symptoms are prevalent, manifold, and sometimes insidious in patients with schizophrenia. In this case study, we reported an intractable headache that bears a close relationship with obsessive-compulsive symptoms in a schizophrenia patient. In a series of treatments, the headache was miraculously susceptible to haloperidol treatment.